Website Design For Estimating Time And Cost Of Replating And Painting Ship Repair at PT.X: Desain Website Estimasi Waktu dan Biaya Pelapisan Ulang dan Pengecatan Perbaikan Kapal di PT.X - WINDA HERDIANTI; ariani Betty; dian prasetyawati; bima azafa (JOINCS (Journal of Informatics, Network, and Computer Science), 2025)
PT. X has been experiencing problems in estimating time and cost data in the replating and painting process on ships. This obstacle is due to the fact that the surveyor owner has difficulty finding data manually which is piled up in the office. Therefore, the researcher designed a website to estimate the time and cost in the process of replating and painting the ship. In this website, the surveyor owner needs to fill the main dimension of the ship data and work. According to the work that has been done, with a comparison of the history of previous work stored on the website, it will speed up the estimation calculation process. The design of this website has been tested on PT. X and get the great result